The role and Importance of Geographic Information Systems in the Field of Transportation(Review paper) (Sebha University Conference Proceedings, 2024)
Roads are among the most critical infrastructures in our lives, upon which we rely heavily for the transportation of goods and commuting. They are the primary means of transportation within and outside cities, thus they must be safe, intact, and free from problems and defects. Consequently, it is essential to adhere to maintenance schedules, ongoing development, and constant planning to ensure that these roads are included in perpetual development and improvement projects. This will ensure a robust transportation system system that fosters prosperity and progress within nations.With the proven importance of Geographic Information Systems (GIS) and their pervasive influence across various fields, particularly in the realm of roads, GIS has been instrumental in solving problems, analyzing data, and facilitating the organization and storage of data efficiently. Its ability to store vast amount of data in a structured and coordinated manner underscores its significance. Therefore, this study aims to review previous research concerning the role of GIS in road engineering, to understand its importance and application in this field, and to compile ideas by presenting a collection of prior studies, thereby elucidating the significant and effective role of GIS.